Seeding future engineers - Evangelista, Tatiane da Silva (2022)
How to motivate female students to progress in the Engineering course? This question was the motivation for this work, which aimed to introduce some women who have revolutionized the world around Exact Sciences to female students attending the Engineering course at the University of Brasilia. This paper presents personal and professional bibliographic results of four extraordinary women scientists in exact sciences: Ada Lovelace, Katherine Johnson, Marie Curie, and Hedy Lamarr and, reports the results of the experience of this work developed in which it concludes benefits of self-esteem, overcoming, courage and appreciation of the female gender, promoting the planting of female engineers.